Practical Unix & Internet Security, 3rd Edition - Garfinkel, Simson (O'Reilly, 2011)
This new edition of Practical Unix & Internet Security provides detailed coverage of today's increasingly important security and networking issues. Focusing on the four most popular Unix variants today--Solaris, Mac OS X, Linux, and FreeBSD--this book contains new information on PAM (Pluggable Authentication Modules), LDAP, SMB/Samba, anti-theft technologies, embedded systems, wireless and laptop issues, forensics, intrusion detection, chroot jails, telephone scanners and firewalls, virtual and cryptographic filesystems, WebNFS, kernel security levels, outsourcing, legal issues, new Internet protocols and cryptographic algorithms, and much more.